Metastatic Adrenocortical Carcinoma Mimicking Pheochromocytoma: The Life-Threatening Cost of Overlooking Clinical Judgment - Castro, Paula; Cardili , Leonardo; Bertacchi, João Guilherme; Costa-Barbosa, Flávia Amanda (Brazilian Journal of Case Reports, 2026)
Adrenocortical carcinoma (ACC) is a rare and aggressive endocrine malignancy with a poor prognosis. Its heterogeneous clinical presentations often mimic more common endocrine disorders, such as polycystic ovary syndrome, Cushing syndrome (SC), thyroid dysfunction, or pheochromocytoma, leading to misdiagnosis and delayed treatment. This report concerns a 34-year-old woman who, despite exhibiting a SC phenotype, virilization, an 11 × 9 × 8 cm left adrenal mass, and multiple lung and liver lesions, was initially diagnosed with metastatic pheochromocytoma based solely on imaging findings and liver biopsy. Only after referral to a tertiary care center was the patient, with an indistinguishable clinical presentation and biochemical profile, identified as ACC, a diagnosis later confirmed through a thorough review of the liver biopsy. Unfortunately, because of the advanced stage of the disease, she was managed with palliative care until her death two weeks after admission. This report underscores the vital importance of clinical judgment in diagnosis, stressing that imaging and fragmented care should never replace a comprehensive clinical evaluation. Even with advanced diagnostic tools, comprehensive clinical evaluation remains essential. Misinterpreting imaging, laboratory, and histopathological results without considering the clinical context can cause delayed diagnoses and poor outcomes, especially in rare and severe endocrine diseases like ACC.